2015
DOI: 10.1111/jch.12637
|View full text |Cite
|
Sign up to set email alerts
|

Management of Hypertensive Patients With Multiple Drug Intolerances: A Single‐Center Experience of a Novel Treatment Algorithm

Abstract: Multiple drug intolerance to antihypertensive medications (MDI‐HTN) is an overlooked cause of nonadherence. In this study, 55 patients with MDI‐HTN were managed with a novel treatment algorithm utilizing sequentially initiated monotherapies or combinations of maximally tolerated doses of fractional tablet doses, liquid formulations, transdermal preparations, and off‐label tablet medications. A total of 10% of referred patients had MDI‐HTN, resulting in insufficient pharmacotherapy and baseline office blood pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 47 publications
0
50
0
Order By: Relevance
“…When drug intolerance is an issue, a recent study by Antoniou et al 33 demonstrated significantly lower blood pressure at 12-month follow-up (by 17±5/9±3 mm Hg) in patients with multiple antihypertensive drug intolerances through the use of sequentially initiated monotherapies, combinations of maximally tolerated doses or fractional tablet doses, liquid formulations, transdermal preparations and off-label tablet medications (figure 2). This was a small (55 patients), non-randomised trial and while promising, should not be considered definitive evidence.…”
Section: Introductionmentioning
confidence: 99%
“…When drug intolerance is an issue, a recent study by Antoniou et al 33 demonstrated significantly lower blood pressure at 12-month follow-up (by 17±5/9±3 mm Hg) in patients with multiple antihypertensive drug intolerances through the use of sequentially initiated monotherapies, combinations of maximally tolerated doses or fractional tablet doses, liquid formulations, transdermal preparations and off-label tablet medications (figure 2). This was a small (55 patients), non-randomised trial and while promising, should not be considered definitive evidence.…”
Section: Introductionmentioning
confidence: 99%
“…A small proportion of patients referred to specialist hypertension services have the added complexity of multidrug intolerance to antihypertensives (MDI-HTN) 48. The utilisation of a novel MDI-HTN stepped treatment algorithm (online supplementary box 3) was able to reduce CBP by 17/9 mm Hg and HBP by 11/12 mm Hg over 6 months.…”
Section: Treatment-resistant Hypertension and Multidrug Intolerancementioning
confidence: 99%
“…Angiotensin converting enzyme inhibitors were discovered as a result of the evidence pointing towards angiotensin-II in pathogenesis of vascular and cardiac hypertrophy [7]. Discovery of multiple antihypertensive drugs have curtailed most deleterious effects of hypertension but much requires to be done as emerging evidence prove some pitfalls in treatment strategies [13].…”
Section: Introductionmentioning
confidence: 99%